Risk factors for myelodysplastic syndromes: a case-control study in Greece. - Dalamaga, Maria; Petridou, Eleni; Cook, Francis E; Dimitrios Trichopoulos (Cancer Causes Control, 2002)
OBJECTIVE: The etiology of most cases of myelodysplastic syndromes (MDS) has not been elucidated. We have undertaken an investigation in Greece to determine the risk profile of adult de-novo MDS. METHODS: A case-control investigation was conducted in a large Veterans' hospital over a five-year period, covering 84 MDS cases and 84 age- and gender-matched controls with minor non-neoplastic non-infectious conditions from the same study base. Cases and controls reported to the medically trained principal investigator lifestyle characteristics and medical histories, with emphasis on autoimmune disorders and allergic conditions. RESULTS: Alcohol intake and tobacco smoking jointly increased significantly the risk of MDS (odd ratio contrasting ever smokers and regular drinkers of at least one glass per day to never smokers and drinkers of less than one glass per day: 9.54. 95% CI 3.52-25.82) whereas each of these factors alone had limited effect. There was also evidence that autoimmune conditions, but not allergic disorders, were positively associated with MDS risk, irrespective of their occurrence during the recent (less than ten years) or the remote (more than ten years) past (OR 3.34, 95% CI 1.15-9.74; OR 3.50, 95% CI 1.19-10.26, respectively). CONCLUSION: We found evidence that both exogenous and endogenous factors may play a role in the etiology of the so-called "de novo" myelodysplastic syndromes, but these findings need further confirmation.
Keywords: Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Case-Control Studies; Cohort Studies; Confidence Intervals; Educational Status; Female; Greece; Humans; Incidence; Logistic Models; Male; Middle Aged; Myelodysplastic Syndromes; Odds Ratio; Risk Factors; Sex Distribution; Smoking; Socioeconomic Factors; Survival Analysis